1998
DOI: 10.1111/j.1365-2036.1998.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant micronutrients and gastric cancer

Abstract: A review of the literature reveals a very consistent association between gastric cancer risk and low intake of fruits and vegetables. This observation has been documented in many countries with different epidemiological techniques: interpopulation correlations, case-control studies and follow up of several cohorts. Low serum levels of beta-carotene and alpha-tocopherol, but not vitamin C, have been reported in patients with gastric dysplasia. Helicobacter pylori infection has been associated with lower concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 21 publications
1
69
1
Order By: Relevance
“…Most of the current literature on carotenoids and GC risk is focused on b-carotene (Correa et al, 1998). This study did not observe any association with plasma levels of a-or b-carotene and GC risk, whereas previous prospective studies have shown lower plasma levels of b-carotene in GC cancer cases vs controls in a Western population (Eichholzer et al, 1996) and either an inverse association (Yuan et al, 2004), no association or a positive association (You et al, 2000) with GC risk in high-risk Chinese populations.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the current literature on carotenoids and GC risk is focused on b-carotene (Correa et al, 1998). This study did not observe any association with plasma levels of a-or b-carotene and GC risk, whereas previous prospective studies have shown lower plasma levels of b-carotene in GC cancer cases vs controls in a Western population (Eichholzer et al, 1996) and either an inverse association (Yuan et al, 2004), no association or a positive association (You et al, 2000) with GC risk in high-risk Chinese populations.…”
Section: Discussionmentioning
confidence: 99%
“…pylori infection has been associated with a decreased level of vitamin C and of major antioxidants (e.g., ␤-carotene) in human gastric tissue (5,26). We found that vitamin C reduced bacterial colonization in the murine stomach and decreased the inflammation score.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction with Helicobacter pylori in stomach cancer has also been suggested to be important (Jacob, 1999). However, chemoprevention trials of stomach cancer in high-risk populations have not conclusively supported a benefit from vitamin C supplements (Blot et al, 1993), although several antioxidant nutrients were associated with regression of gastric dysplasia (Correa et al, 2000). Vitamin C also interacts with iron to promote oxidative damage (Jacob, 1999).…”
Section: Antioxidantsmentioning
confidence: 99%